2009
DOI: 10.1074/jbc.m109.020032
|View full text |Cite
|
Sign up to set email alerts
|

The Linker Region in Receptor Guanylyl Cyclases Is a Key Regulatory Module

Abstract: Receptor guanylyl cyclases are multidomain proteins, and ligand binding to the extracellular domain increases the levels of intracellular cGMP. The intracellular domain of these receptors is composed of a kinase homology domain (KHD), a linker of ϳ70 amino acids, followed by the C-terminal guanylyl cyclase domain. Mechanisms by which these receptors are allosterically regulated by ligand binding to the extracellular domain and ATP binding to the KHD are not completely understood. Here we examine the role of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 51 publications
4
53
0
Order By: Relevance
“…A single transmembrane domain is followed by a pseudokinase domain with sequence similarity to protein kinases (16,17). The C-terminal guanylyl cyclase domain is linked to the kinase homology domain by a linker region (18). We have shown that the kinase homology domain binds ATP and mutation of a critical lysine residue involved in interacting with the ␤-phosphate of ATP prevents ligand-mediated activation of GC-C (16).…”
Section: Guanylyl Cyclase C (Gc-c) Is a Multidomain Membrane-associamentioning
confidence: 99%
See 3 more Smart Citations
“…A single transmembrane domain is followed by a pseudokinase domain with sequence similarity to protein kinases (16,17). The C-terminal guanylyl cyclase domain is linked to the kinase homology domain by a linker region (18). We have shown that the kinase homology domain binds ATP and mutation of a critical lysine residue involved in interacting with the ␤-phosphate of ATP prevents ligand-mediated activation of GC-C (16).…”
Section: Guanylyl Cyclase C (Gc-c) Is a Multidomain Membrane-associamentioning
confidence: 99%
“…We have shown that the kinase homology domain binds ATP and mutation of a critical lysine residue involved in interacting with the ␤-phosphate of ATP prevents ligand-mediated activation of GC-C (16). The linker region appears to adopt a helical structure and extensive mutational analysis demonstrated the critical requirement of the linker in repressing the guanylyl cyclase activity of the receptor in the absence of its ligands (18).…”
Section: Guanylyl Cyclase C (Gc-c) Is a Multidomain Membrane-associamentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic mutational and biochemical analyses of GC-C and GC-A have suggested an important role for the linker region in repressing the catalytic activity of the receptors in the absence of their ligands (133). Specific residues in the linker region seem to assist in repressing GC activity through its interaction with the GCD, where Gα may also interact with and activate (or inhibit) rGC.…”
Section: Mechanism Of Activation Of Rgcsmentioning
confidence: 99%